MHD turbulence: Nonlocal, anisotropic, nonuniversal? - Schekochihin, A; Cowley, S; Yousef, T (2008)
Kolmogorov's theory and philosophy of turbulence are based on a number of assumptions that have become standard notions with which one approaches turbulence in many, including non-hydrodynamic, systems. However, it turns out that in MHD turbulence, locality of interactions in scale space, isotropy of small scales or even universality cannot be taken for granted and, in fact, can be shown to fail. This note focuses on these unconventional aspects of MHD turbulence and on the related phenomenon of small-scale dynamo using a combination of simple physical reasoning and numerical evidence. © 2008 Springer.